A Study of Conceptual Metonymy of Embodiments in English and Vietnamese - Nguyen Thi Tuyen (University of Foreign Language Studies - The University of Danang, 2024)
Chapter 1: Introduction. Chapter 2: Literature review and theoretical Background. Chapter 3: Methodology and procedures...